Akibat Hukum Pewarisan Adat Tunggu Tubang pada Suku Semendo - Tsania Manzil Assolich; Talitha Nabilah; Achmad Ichsan Maliki; Wiwin Yulianingsih (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
Inheritance law is actually part of civil law. One of the systems of inheritance for the adat waiting for tubang is implemented in the Semendo Tribe, South Sumatra. The customary inheritance law system in Indonesia is influenced by differences in kinship arrangements in society which are illustrated by the existence of patrilineal, matrilineal and parental systems of descent. Based on this, then it is worth exploring regarding the implementation of the Wait Tubang inheritance in the Semendo Tribe in the customary inheritance system in Indonesia as well as legal consequences for assets and their heirs. This research is an urgency to be carried out, in order to provide an understanding of legal certainty regarding the customary inheritance system from a civil or nationally applicable legal perspective, in which legal certainty can become a provision for further research. This research is normative juridical type. Approach to statutory regulations and concept approach used in this study. The results of the study found that the application of the legal system of customary inheritance for the Semendo tribe is inherent in the matrilineal descent system, where the first daughter is "waiting for tubang". The oldest son is only a companion for 'Apik Jurai' or as a supervisor of the heirs for his inheritance. The legal consequence is that it is attached to the female heir. This is inversely proportional to the position of women in civil law in Indonesia, which can actually be categorized as incapable of law as referred to in Articles 105 and 108 of the Indonesian Civil Code. The customary law inheritance system in Indonesia, including the Tunggu Tubang, must be given specific legal protection by the government as well as supervision. The community must understand more about the diversity of customs in Indonesia. The legal position of customary inheritance thus becomes an urgency for legal certainty to be more secure.